Differentiation in the classroom. (1st April 2019) - Bromley, Matt
Abstract : If we are to ensure that every pupil can make progress then a key skill for every teacher is the art of differentiation, both in their lesson planning and their teaching. For this SecEd Best Practice Focus, Matt Bromley discusses practical approaches for effective differentiation